Students’ Conceptions of Learning Using Animations - Nursamiha Awang Morsid; Sallimah M. Salleh; Masitah Shahrill (Universitas Syiah Kuala, 2020)
This study explored the integration of animations in lessons designed using the Technological, Pedagogical, Content Knowledge (TPACK) framework to enhance students’ conceptual understanding in the processes of diffusion and osmosis. The study was conducted in a secondary school involving 22 Year 12 students. Data was collected using the Osmosis and Diffusion Conceptual Assessment (ODCA), which is a two-tier diagnostic test administered before and after the lessons. The lessons were designed using an action research cycle, integrated with the TPACK matrix. There were four cycles to address the students’ knowledge dimension, which scaffolds from lower order thinking to higher order thinking (declarative, procedural, schematic and strategic). The paired sample t-test was used to analyse the data and the findings revealed significant differences in the students’ conceptual understanding after the animation-integrated lessons were carried out. The intervention was successful as proven from the large effect size, together with the increased frequency of students having selected the correct responses in the ODCA.